Clinical and pathological features of myeloid leukemia cutis - Li Li; Yanan Wang; Christine Guo Lian; Nina Hu; Hongzhong Jin; Yuehua Liu (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Myeloid leukemia cutis is the terminology used for cutaneous manifestations of myeloid leukemia. Objective: The purpose of this study was to study the clinical, histopathological and immunohistochemical features of myeloid leukemia cutis. Methods: This was a retrospective study of clinical and pathological features of 10 patients with myeloid leukemia cutis. Results: One patient developed skin lesions before the onset of leukemia, seven patients developed skin infiltration within 4-72 months after the onset of leukemia, and two patients developed skin lesions and systemic leukemia simultaneously. Of these patients, five presented with generalized papules or nodules, and five with localized masses. The biopsy of skin lesions showed a large number of tumor cells within the dermis and subcutaneous fat layer. Immunohistochemical analysis showed strong reactivity to myeloperoxidase (MPO), CD15, CD43 and CD45 (LCA) in most cases. NPM1 (nucleophosmin I) and FLT3-ITD (Fms-like tyrosine kinase 3-internal tandem duplication) mutations were identified in one case. Five patients with acute myelogenous leukemia and one patient with chronic myelomonocytic leukemia died within two months to one year after the onset of skin lesions. Study limitations: This was a retrospective and small sample study. Conclusions: In patients with myelogenous leukemia, skin infiltration usually occurs after, but occasionally before, the appearance of hemogram and myelogram abnormalities, and the presence of skin infiltration is often associated with a poor prognosis and short survival time. myeloid leukemia cutis often presents as generalized or localized nodules or masses with characteristic pathological and histochemical findings.